Systematic review: e-cigarettes vs. conventional cigarettes - Janik, Mateusz; Ufnalska, Barbara; Rychlewska-Duda, Joanna; Lisiecka, Justyna; Fabijański, Artur; Konarska, Anna; Machowiak, Anna; Nowak, Michał; Firlej, Wojciech; Dukacz, Adrianna (Journal of Education, Health and Sport, 2025)
Introduction Electronic cigarettes have gained widespread popularity by being marketed as a safer alternative to traditional smoking. Possibility of inhaling vapor created by heating nicotine liquid instead of combusting tobacco leaves revolutionized tobacco market, bringing a lot of questions about harmfulness or advantages of e-cigarettes. Their popularity is increasing and many aspects about their influence on health are still unclear. At the same time, better social acceptance than tobacco cigarettes brings out questions if they are a step to smoking cessation or if they encourage more people to start using nicotine. Aim of the review This systematic review provide an analysis of the existing literature on the influence of e-cigarettes on the human body with their economic and behavioral aspects. By examining a wide range of studies, we aim to elucidate the potential risks and benefits associated with e-cigarette use and provide a comparison of both electronic and conventional forms of nicotine consumption. Methods A systematic search was conducted using electronic databases such as PubMed, Scopus, and Web of Science. Keywords included "e-cigarettes", "vaping", "health effects", "conventional cigarettes", "tobacco", "respiratory system", "cardiovascular system", "immune system", "oral health", and "cellular effects". The search was limited to studies published up to December 2023. Both observational and experimental studies were included. Conclusion While e-cigarettes are often promoted as a safer alternative to conventional cigarettes, the evidence suggests that they are not without significant health risks. It is important to remember that they are a new form of substance use, and many aspects related to them are still unknown. E-cigarettes and conventional cigarettes present distinct usage patterns and cost profiles. Years of research on larger sample sizes are needed to determine their impact on humans.